More, Better, or Different Spending? Trends in Public Expenditure on Water and Sanitation in Sub-Saharan Africa - van Ginneken, Meike; Netterstrom, Ulrik; Bennett, Anthony (World Bank, Washington, DC, 2014)
This overview paper tests current public spending patterns against the economic rationale for such spending, including reducing disparities in service delivery and overcoming market failures. Reducing the disparities in access to basic water supply and sanitation (WSS) is a responsibility of government. Individuals have little incentive to build and maintain extensive WSS infrastructure, but communities and societies do. Targeted public spending benefitting households that otherwise would be unable to afford those services can be a component of a broader social policy agenda to redistribute resources to the poor. Several market features call for government intervention in the WSS sector. This review mines the rich data of 15 Public Expenditure Reviews (PERs) conducted in Sub-Saharan Africa and funded by the World Bank over the past years. From 2003 the World Bank has funded more than 40 PERs that contain an analysis of the water supply and sanitation (WSS) sector. In most of these, the WSS sector is discussed alongside other sectors. A set of stand-alone PERs specifically addressing the WSS sector have also been carried out in African countries. The scope of the present review includes expenditures by public institutions (at the central and local government levels) on domestic resources and grants or loans provided by external funding agencies. The review does not include off-budget spending by water utilities. In other words, while the numbers in this review include public subsidies to utilities, they do not include expenditure by utilities, thus disregarding expenditures paid for by consumer cost-recovery. The public expenditure analyses in all reviews focus on WSS services, although some reports also discuss water resources management. Almost all of the PERs, however, are limited to WSS, thus excluding water resources management and irrigation issues from the analyses. The reviewed PERs did not use standard definitions, which has led to some data limitations described later. This review is a data mining exercise of country PERs that were written to serve in the political dialogue on the challenges in achieving the Millennium Development Goals (MDGs) by 2015 and on bottlenecks in enhancing public finance management performance.